Genistein Effect on Estrogen Receptor especially Interleukin-6 and Tumor Necrosis Factor-α in Mice Model of Endometriosis: a Systematic Review and Meta-analysis - Sutrisno Sutrisno; Lovin Destikatari (Asian Journal of Health Research, 2023)
Introduction: Endometriosis is the endometrial tissue proliferation outside the uterine space. Anti-angiogenic agents from different groups of substances are currently being discussed as promising therapies for the treatment of endometriosis in the future, one of which is therapy using the phytoestrogen genistein. At the molecular level, genistein's effects on cells include inhibition of proliferation, induction of differentiation, apoptosis, and cell arrest in the cell cycle, which are related to the transforming growth factor. Genistein inhibits cell growth by modulating the signal-transforming growth factor pathway. Methods: We searched PubMed, Scopus, Cochrane Library and Proquest from its inception to December 2022 to collect observational and interventional studies of Genistein consumption in endometriosis mice. Two authors independently screened the literature according to the inclusion and exclusion criteria, extracted data, and assessed the risk of bias. Safety analysis was assessed through TNF-α and IL-6 values of estrogen expression. Results: No significant difference in the values of IL-6 and TNF-α in rats with endometriosis that were given genistein at these three doses. However, if analyzed further, the IL-6 outcome compared to the 0.78mg/day dose most affected the IL-6 value between the two groups, and the TNF-α output compared to the 0.78 mg/day dose most affected the TNF-α value between the two groups. So, a genistein dose of 0.78 mg/day can affect IL-6 and TNF-α in mice with endometriosis. Conclusion: Genistein modulated estrogen expression of TNF-α and IL-6 at all doses, but the best dose for its effect was 0.78 mg/day.